2000
DOI: 10.1097/00003226-200011000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Transketolase Gene Expression in the Cornea Is Influenced by Environmental Factors and Developmentally Controlled Events

Abstract: Our studies suggest that both exposure to incident light and events surrounding the process of eyelid opening play a role in the up-regulation of TKT gene expression observed during corneal maturation in mice. Light appears to play a less important role in the mature cornea in maintaining high levels of TKT gene expression. The low levels of TKT in the cornea of chicken and zebrafish support the notion that TKT acts as a taxon-specific enzyme-crystallin in mammals. The involvement of environmental signals for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…In the second group of proteins, which includes keratins 3 (Chaloin-Dufau et al, 1990;Rodrigues et al, 1987) and 12 (Chaloin-Dufau et al, 1990;Liu et al, 1993), transketolase (Sax et al, 2000), connexin 43 (Wolosin et al, 2002), and aldehyde dehydrogenase (Burton et al, 1999;Downes and Holmes, 1992;Kays and Piatigorsky, 1997), increased expression has been observed in conjunction with eyelid opening. These proteins exhibit a reciprocal localization with those in the first group, in that they are present at low levels at birth and increase as the epithelium stratifies and matures.…”
Section: Epithelial Differentiation Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second group of proteins, which includes keratins 3 (Chaloin-Dufau et al, 1990;Rodrigues et al, 1987) and 12 (Chaloin-Dufau et al, 1990;Liu et al, 1993), transketolase (Sax et al, 2000), connexin 43 (Wolosin et al, 2002), and aldehyde dehydrogenase (Burton et al, 1999;Downes and Holmes, 1992;Kays and Piatigorsky, 1997), increased expression has been observed in conjunction with eyelid opening. These proteins exhibit a reciprocal localization with those in the first group, in that they are present at low levels at birth and increase as the epithelium stratifies and matures.…”
Section: Epithelial Differentiation Markersmentioning
confidence: 99%
“…Potential environmental cues include changes in light and oxygen. To examine the potential role of light in the expression of the epithelial differentiation marker transketolase, Sax et al (Sax et al, 2000) compared mice reared in the dark to their normal littermates. They observed that the level of transketolase mRNA was two-fold lower in the dark-raised mice, indicating that light was a stimulus.…”
Section: A B C D E F G H Regulation Of Gene Expression Associated Witmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that light may be involved in the coordination of corneal gene expression with eyelid opening. Sax et al, (2000) report that developmentally dependent expression of corneal transketolase is partially inhibited in animals maintained in the dark for the first four weeks of life.…”
Section: Qin Et Al (1997) Examined Changes In Laminin and Collagenmentioning
confidence: 99%
“…23 In support of this hypothesis, expression of corneal crystallins has been shown to be environmentally and developmentally regulated with a marked increase in expression after eyelid opening, exposure to light, and development of corneal transparency. 24,25 From the …”
mentioning
confidence: 99%